University Ranking and Information Disclosure: The Case of Indonesia - Pujiningsih, Sri; Utami, Helianti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to explore the information disclosure level of universities in Indonesia andits relationship with university ranking. Data were collected from universities reportspublished in their website from 2018 to 2020 (53 Observations). Using content analysis andregression tests, this study found a low level of information disclosure in universities inIndonesia. The disclosure of sustainability aspect is the lowliest level (9%) compared to theother information disclosures. The intellectual capital disclosure is not explicitly stated inthe universities reports. The results of the regression test confirmed that the universitiesranking have a positive effect on the universities disclosure level. The study supports theapplicability of the signal theory in the context of higher education institutions.